Control of the leishmaniases (WHO GenevaCH, 2010)
Includes new therapeutical recommendations for visceral and cutaneous leishmaniasis, recommendations on the use of rapid diagnostic tests, details on the management of Leishmania-HIV co-infection and consideration of social factors and climate change as risk factors for increased spread.
Keywords: LEISHMANIASIS